Mini Riset: Pengaplikasian Kurikulum Merdeka Belajar Kelas VII dan VIII di SMP Unggulan Aisyiyah, Bantul - Akmal Bary; Hujjatul Fakhrurridha; Sabarudin (LPPM Politeknik Pratama, 2024)
This study aims to examine the implementation of the Merdeka Belajar Curriculum in the seventh and eighth grades at Aisyiyah Outstanding Junior High School in Bantul. The Merdeka Belajar Curriculum is an educational innovation designed to provide students with the freedom to manage their own learning processes. This research utilizes a descriptive qualitative method, with two key informants, namely the deputy headmaster responsible for the curriculum and a teacher of Islamic Education (PAI). Data collection techniques include literature review from books, articles, and relevant documents, as well as document analysis to gain a comprehensive understanding of the curriculum implementation. The findings of this research provide insights into the extent of the implementation of the Merdeka Belajar Curriculum at Aisyiyah Outstanding Junior High School, particularly in the seventh and eighth grades. These findings are expected to contribute to the development of the implementation of the Merdeka Belajar Curriculum at the junior high school level and offer valuable information for decision-makers regarding education in this school. The research also identifies supportive and hindering factors in the implementation of the Merdeka Belajar Curriculum, providing in-depth insights for the improvement and enhancement of educational policies in the future.